Jump performance and force-velocity profiling in high-level volleyball players: A pilot study - Broussal-Derval, A.; Delacourt, L.; Samozino, P.; Morin, J.-B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Jump performance is the most important physical determinant of volleyball (VB) performance, at all levels of play (Ziv and Lidor, 2010). Research and practice have long sought to improve players jump height through specific strength training (Newton et al., 2006). Recently, the concept of optimal force-velocity (FV) profile has been related to jump performance: in addition to maximal lower limbs power (Pmax), a well-balanced FV profile is a key factor (Samozino et al., 2014). We investigated jump performance, Pmax and FV imbalance in pre-professional and professional VB players. Methods: Using a simple method based on five loaded squat jumps, we determined Pmax and the FV imbalance (FVimb), i.e. the % difference between a player`s actual and optimal FV profiles (Samozino et al., 2014) in the following groups: young elite (32 females, 22 males), professional (6 females, 8 males), professional in beach-VB (5 males). Results: In both female and male players, jump height increased with the level of play (from 26.6 cm in young females to 37.8 cm in pro beach-VB males), as did Pmax (from 23.2 to 31.0 W/kg). All the groups tested showed on average a FVimb towards a deficit in maximal force capability. This FVimb was very similar between groups: -37 and -34% for female young and professional players, and -34 and - 33% for male young and professional players, respectively. Interestingly, these FVimb were very variable within groups (coefficients of variation of 37 to 150%). Additional computations showed that on average, 10.4 % better jump heights (range: 0-38%) could be expected in these players should FVimb be reduced, all other things (e.g. Pmax) being equal. Discussion: This pilot study provides a descriptive reference for young and professional high-level VB players, and paves the way for more individualized training programs. Indeed, we observed that the majority of players had a force deficit (negative FVimb), which means that, ceteris paribus, a force-oriented training program would result in improved jump performance in most players. However, the interest of this approach is that some players had an optimal FV profile and even a velocity deficit (high within-group variability), which means they would benefit from a different strength training than the majority of their teammates. This study supports the interest of an individualized FV profiling and strength work to improve jump height in VB players.